2013
DOI: 10.3390/molecules181012751
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Molecular Crowding on the Stability of Human c-MYC Promoter Sequence I-Motif at Neutral pH

Abstract: Abstract:We have previously shown that c-MYC promoter sequences can form stable i-motifs in acidic solution (pH 4.5-5.5). In terms of drug targeting, the question is whether c-MYC promoter sequence i-motifs will exist in the nucleus at neutral pH. In this work, we have investigated the stability of a mutant c-MYC i-motif in solutions containing a molecular crowding agent. The crowded nuclear environment was modeled by the addition of up to 40% w/w polyethylene glycols having molecular weights up to 12,000 g/mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
127
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 58 publications
(67 reference statements)
8
127
0
Order By: Relevance
“…S9A). Because the higher molecular weight of PEG shows more stabilization of i-motif due to the excluded volume effect (23,24), the replication might not be effectively stalled by the addition of 20 wt% PEG200. In fact, the addition of 20 wt% PEG200 did not increase thermal stability of the (C 3 TA 2 ) 4 i-motif, whose T m was 28.7°C and −ΔG°3 7 was −1.4 kcal·mol −1 (SI Appendix, Table S2).…”
Section: Dependence Of Replication Efficiency On I-motif Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…S9A). Because the higher molecular weight of PEG shows more stabilization of i-motif due to the excluded volume effect (23,24), the replication might not be effectively stalled by the addition of 20 wt% PEG200. In fact, the addition of 20 wt% PEG200 did not increase thermal stability of the (C 3 TA 2 ) 4 i-motif, whose T m was 28.7°C and −ΔG°3 7 was −1.4 kcal·mol −1 (SI Appendix, Table S2).…”
Section: Dependence Of Replication Efficiency On I-motif Stabilitymentioning
confidence: 99%
“…S9E). Although the detailed mechanism of stabilization of the i-motif structure by PEG1000 is unknown, the higher molecular-weight PEG shifts the pK a of N3 in the cytosine base (23,24). As the i-motif structure is very compact compared with a random coil, a more pronounced excluded volume effect of higher molecular-weight PEG1000 compared with that of PEG200 may contribute to the observed effect of PEG1000 on the replication of an i-motif-forming DNA.…”
Section: Dependence Of Replication Efficiency On I-motif Stabilitymentioning
confidence: 99%
“…[16] i-Motifs can also exist at neutralp Hu nder molecular crowded conditions [17] and under transcriptionally induced negative superhelicity. [18] The recent remarkable finding that the transcription of centromeric alpha-satellite DNA during mitosis is required for centromere function [19] supports the conclusion that negative superhelicity conditions may be commoni nt hese regions and, consequently,f avor i-motif formation under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…15 Nevertheless, only a few studies reported the i-motif folding at neutral pH. [16][17][18] In this study, we http://dx.…”
Section: Introductionmentioning
confidence: 90%